Tripterygium drug-loaded liposome alleviates renal function by promoting vascularization and inhibiting fibrosis - Chen, Ziwei; Wang, Jiajia; Zhou, Jianyu; Yu, Haifeng; Zheng, Lu; Chen, Yuan; Wan, Xiaoqing; Zhang, Wei (Frontiers in Chemistry, 2024)
Introduction: Tripterygium species have been traditionally used in Chinese medicine for treating various conditions. The aim of the study was to construct a drug-modified renal infarction targeting liposome (rTor-LIP) containing Tripterygium in order to improve the therapeutic effect on renal injury. Methods: rTor-LIP was prepared using the extruder method containing Tripterygium solution. The preparation was characterized by transmission electron microscopy, Marvin laser particle size analyzer, and Western blotting. In vitro experiments were conducted to verify the biocompatibility of rTor-LIP, and in vivo experiments were conducted to verify the therapeutic effect of rTor- LIP on renal injury. Results and discussion: The surface of rTor-LIP was regular and oval. In vitro results showed that after co-incubation with rTor-LIP, endothelial cells did not show significant apoptosis, and there were no significant abnormalities in the mitochondrial metabolism. The in vivo results showed that the morphology of endothelial cells in the rTor-LIP group was uniform and the cytoplasmic striations were clear, but the local striations had disappeared. Thus, rTor-LIP nano-targeted liposomes can effectively target hypoxic kidney tissue, providing a new idea for the treatment of renal infarction.